2009
DOI: 10.1007/s12237-009-9200-x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Forcing of Phytoplankton in a Mediterranean Estuary (Guadiana Estuary, South-western Iberia): A Decadal Study of Anthropogenic and Climatic Influences

Abstract: Phytoplankton seasonal and interannual variability in the Guadiana upper estuary was analyzed during 1996-2005, a period that encompassed a climatic controlled reduction in river flow that was superimposed on the construction of a dam. Phytoplankton seasonal patterns revealed an alternation between a persistent light limitation and episodic nutrient limitation. Phytoplankton succession, with early spring diatom blooms and summer-early fall cyanobacterial blooms, was apparently driven by changes in nutrients, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 106 publications
(186 reference statements)
2
50
0
1
Order By: Relevance
“…In particular, phytoplankton merits special attention being generally the dominant primary producer in most aquatic ecosystems. Situated at the base of the food web, phytoplankton is linked to the biogeochemical cycles and energy flux; all changes in phytoplankton composition, abundance and distribution may have cascading effects along the trophic food web (Barbosa et al, 2010). Phytoplankton is considered to be good indicators of climate change, which may alter the structure and dynamics of aquatic ecosystems (Hays et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, phytoplankton merits special attention being generally the dominant primary producer in most aquatic ecosystems. Situated at the base of the food web, phytoplankton is linked to the biogeochemical cycles and energy flux; all changes in phytoplankton composition, abundance and distribution may have cascading effects along the trophic food web (Barbosa et al, 2010). Phytoplankton is considered to be good indicators of climate change, which may alter the structure and dynamics of aquatic ecosystems (Hays et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…65% -89% of total inorganic N), showed a decreasing trend after construction of Alqueva dam (see As referred in previous studies (Barbosa et al, 2010), silicate concentration was usually correlated with rainfall and river flow, and negatively correlated to chlorophyll a. Both DSi and nitrate exhibited seasonality with higher values during winter and lower values between midspring and summer.…”
Section: Resultsmentioning
confidence: 60%
“…These authors also referred that cyanobacteria dominated the chlorophyll maximum zone in the upper estuary in late summer-early fall, due to warm waters, reduced sinking and grazing, as well as N limitation with low N:P ratio. Nitrogen limitation during summer increased in the period after Alqueva in the upper estuary (Barbosa et al, 2010). Additionally, nutrient enrichment experiments performed during 2008 clearly demonstrated that phytoplankton growth was nitrogen limited (Domingues et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is a sensitive bio-indicator of ecosystem general health, its nutrient status, eutrophication, pollutants, and other anthropogenic impacts in aquatic environments [3]. As primary producer, it is capable of responding to changes in nutrient and toxin input, hydrology, sedimentation, irradiance and temperature regimes over a wide range of time scales.…”
Section: Introductionmentioning
confidence: 99%